L1000 Viewer: A Search Engine and Web Interface for the LINCS Data Repository - Musa, Aliyu; Tripathi, Shailesh; Dehmer, Matthias; Emmert-Streib, Frank (Frontiers in Genetics, 2019)
The LINCS L1000 data repository contains almost two million gene expression profiles for thousands of small molecules and drugs. However, due to the complexity and the size of the data repository and a lack of an interoperable interface, the creation of pharmacologically meaningful workflows utilizing these data is severely hampered. In order to overcame this limitation, we developed the L1000 Viewer, a search engine and graphical web interface for the LINCS data repository. The web interface serves as an interactive platform allowing the user to select different forms of perturbation profiles, e.g., for specific cell lines, drugs, dosages, time points and combinations thereof. At its core, our method has a database we created from inferring and utilizing the intricate dependency graph structure among the data files. The L1000 Viewer is accessible via \url{http://turing.devcrew.co.uk}.